Rethinking Penal Abolitionism in Argentina Tactics and Strategies (Delito y Sociedad, 2021)
The recent momentum gained by the abolitionist movement in other countries, perhaps as a consequence of state violence and the debacle that the pandemic has brought into prisons, constitutes a good excuse to rethink the perspectives of the movement in Argentina. Although the influence of penal abolitionism has been important locally on a theoretical level, and may have indirectly fostered significant procedural reforms, it has not been a determinant in legal and political practice, nor has it been generative of substantial social or institutional transformations that modified the dynamics of our penal systems. In this paper, we sketch out the situation of abolitionism in Argentina and suggest adaptations that penal abolitionism could make to face local challenges and advance an abolitionist agenda. Using tools from critical legal theories and following the recent examples of the local human rights and feminist movements, we argue that abolitionism could develop a tactical use of the criminal justice system and implement forms of communication to produce counter-narratives of crime and criminalization.
Keywords: Penal abolitionism; human rights and feminist movements; tactical use of the criminal justice system; counter-narratives of crime; mestizo penal abolitionism